Morphometry and redescription of Parahelichus granulosus (Delève, 1974) with description of P. pseudogranulosus, a new cryptic species of Long-toed Water Beetles (Coleoptera: Dryopidae) from Indochinese peninsula, and proposal of a new synonym for Praehelichus sericatus (Waterhouse, 1881) from China - Lojková, Soňa; Degma, Peter; Kodada, Ján (Zootaxa, 2014)
A new species of Parahelichus Löbl & Smetana, 2006 is described from Laos and Thailand: P. pseudogranulosus. A similar species, P. granulosus Delève, 1974, which was originally described only from a single specimen, is redescribed and morphometric data are provided from 442 specimens from Vietnam and Laos. Habitus views, illustrations of important characters as well as results of morphometric analyses are presented and discussed. Praehelichus sinensis (Fairmaire, 1888) is proposed as a new junior synonym of P. sericatus (Waterhouse, 1881).